Synthesis and characterization of turbostratic carbons prepared by catalytic chemical vapour decompostion of acetylene - Li, L.; Zhu, Z.; Lu, G.; Yan, Z.; De Marco, Roland (Elsevier B.V., 2006)
The turbostratic mesoporous carbon blacks were prepared by catalytic chemical vapour decomposition (CCVD) of acetylene using Ni/MgO catalysts prepared by co-precipitation. The relationship between deposition conditions and the nanostructures of resultant carbon black materials was investigated. It was found that the turbostratic and textural structures of carbon blacks are dependent on the deposition temperature and nickel catalyst loading. Higher deposition temperature increases the carbon crystallite unit volume Vnano and reduces the surface area of carbon samples. Moreover, a smaller Vnano is produced by a higher Ni loading at the same deposition temperature. In addition of the pore structure and the active metal surface area of the catalyst, the graphitic degree or electronic conductivity of the carbon support is also a key issue to the activity of the supported catalyst. Vnano is a very useful parameter to describe the effect of the crystalline structure of carbon blacks on the reactivity of carbon blacks in oxygen-carbon reaction and the catalytic activity of carbon-supported catalyst in ammonia decomposition semi-quantitatively.